EFFICACY OF USING A MULTIVITAMIN COMPLEX IN CHILDREN WITH ALLERGIC DISEASES - V.F. Lapshin (Педиатрическая фармакология, 2010)
Efficacy of using a multivitamin complex in children with allergic diseases requires a pediatrician to pay special attention. The pharmaceutical market is flooded with various preparations of this group. The physician faces the issue of a difficult choice in prescribing an efficient and safe multivitamin agent for a child with co-morbidity. The article provides results of a clinical study for the efficacy and tolerance to a multivitamin complex in children with allergic diseases. It is found that its use in an integrated treatment course helped to improve the efficacy of pathogenetic therapy in the children studied and to correct the symptoms of hypovitaminosis. Good tolerance to the agent under study and no side effects in examined children are demonstrated. Key words: allergic diseases, hypovitaminosis, vitamin and mineral complexes, children. (Pediatric Pharmacology. – 2010; 7(2):102-104)